Spectrophotometric Determination of Bendiocarb in Insecticidal Formulations, Grains and Water - Naidu, N.V.S.; Naidu, P.R. (Asian Journal of Chemistry, 2012)
A simple rapid and sensitive spectrophotometric method is described for the determination of Bendiocarb. The phenol formed due to alkaline hydrolysis of Bendiocarb is made to couple with diazotized p-aminobenzene sulfonamide to give coloured species having an absorption maximum at 448 nm. Beer’s law is obeyed over the range 0.5 to 12 ppm.